Tunka Advanced Instrument for cosmic rays and Gamma Astronomy (TAIGA): Status, results and perspectives - Kuzmichev L.; Astapov I.; Bezyazeekov P.; Boreyko V.; Borodin A.; Brückner M.; Budnev N.; Chiavassa A.; Gress O.; Gress T.; Grishin O.; Dyachok A.; et al. (EPJ Web of Conferences, 2017)
We present the current status of high-energy cosmic-ray physics and gamma-ray astronomy at the Tunka Astrophysical Center (AC). This complex is located in the Tunka Valley, about 50 km from Lake Baikal. Present efforts are focused on the construction of the first stage of the gamma-ray observatory TAIGA - the TAIGA prototype. TAIGA (Tunka Advanced Instrument for cosmic ray physics and Gamma Astronomy) is designed for the study of gamma rays and charged cosmic rays in the energy range 1013 eV–1018 eV. The array includes a network of wide angle timing Cherenkov stations (TAIGA-HiSCORE), each with a FOV = 0.6 sr, plus up to 16 IACTs (FOV - 10∘× 10∘). This part covers an area of 5 km2. Additional muon detectors (TAIGA-Muon), with a total coverage of 2000 m2, are distributed over an area of 1 km2.